Refractive Index and Density Measurements of Peanut Oil for Determining Oleic and Linoleic Acid Contents. (4th November 2012) - Davis, Jack P.; Sweigart, Daniel S.; Price, Kristin M.; Dean, Lisa L.; Sanders, Timothy H.
Abstract: Peanut seed are approximately 50 % oil of which >80 % is either oleic or linoleic acid. The oleic/linoleic acid ( O / L ) ratio largely influences oxidative stability and hence peanut shelf life. Traditional peanut seed have O / L ratios near 1.5–2.0; however, many new cultivars are "high oleic" with O / L ratios ≥9. During peanut seed handling, contamination among lots may occur. A cost effective method to rapidly differentiate peanut seed based on O / L ratio is needed across multiple segments of the industry, and measurements of oil density and oil refractive index (RI) were evaluated for this potential. Fatty acid profiles of samples from normal and high oleic seed lots, and blends of these oils, were determined by traditional gas chromatography analysis and this data compared to corresponding oil density and RI measurements. Oleic acid content, linoleic acid content, density and RI were all strongly linearly ( R 2 > 0.98) correlated for oil blends with O / L ratios from ~2 to 16. Threshold density or RI values both showed excellent potential for rapidly differentiating samples with an O / L ≥ 9; however, sample volume requirements preclude density measurements on single seed.